Punctate analysis using Oneota ceramics from La Crosse, Wisconsin - Oberreuter, Sheila M. (My University, 2010)
The Oneota material culture is found throughout the Upper Midwest, clustering around certain areas that supply vital resources, one of these areas being the modern day city of La Crosse, Wisconsin. The La Crosse locality Oneota lived in the area from A.D. 1300-1625. This study looks at punctates on Oneota ceramics to try to identify if the same tool can be identified at two sites in the La Crosse locality. Finding this would imply that communication or interaction was occurring between these two sites.
Keywords: Pottery, Prehistoric -- Wisconsin.; Oneota Indians (Great Plains) -- Antiquities.